A short review on Islamic perspective related to knowledge, attitude and attitudes practice towards vaccination - E. Zainudin, Engku Nuraishah Huda; Shahdan, Intan Azura (2016)
Study aims: UNICEF reported pneumonia remains one of the single largest killers of young children worldwide regardless of steady development of the nation. Diarrheal disease comes as second contributor. The preventive measure through vaccination program is one method that can decrease mortality rate. However, increasing number of parents are refusing vaccines. The authors agree vaccination which is an important intervention correlate well with the priorities of Islamic jurisprudence (Maqasid as-Shariah); the preservation of life comes only second after the preservation of Deen. From Islamic points of view, life is a gift from Allah (SWT) and its protection and continuation is of greatest value and need. Therefore, Tthis preliminary and on-going study has the objective to firstly, investigate and evaluate knowledge, awareness attitude and perception from parents on vaccination, and secondly, to understand the Islamic worldview in vaccination. Methods: A short review was performed through PubMed and Scopus scientific databases. Simultaneously, an on-going survey study is performed to determine teachers and parents perception towards vaccination. Results: Overall, several papers were reviewed for this short review. A lack of knowledge on vaccination purpose, contents and effects were noticed. Parents’ decision to vaccinate their children can be influenced by the followings; religion and ethnicity (Bray & Keating, 2012; Forster et al., 2016), upbringing and migration factors (Colgrove 2006), and concern on the side effects. Some parents resist to vaccinate their children due to the ‘halalness’ issue of the vaccine and believing that vaccine could do more harm than good (Personal communication between author with parents attending public health clinic in Kuantan, Pahang). Conclusions: It would be essential to strengthen educational initiatives in the clinic and community to correctly inform patients on the important of vaccination. The Islamic inputs such as ‘istihalah’ in vaccine manufacturing should be explained in order to increase their understanding towards this matter.